PENERAPAN MEDIA KOMIK PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Nugraheni, Nursiwi (Universitas Muria Kudus, 2017)
This study aims to determine: (1) how to implement comic media of mathematics learning in primary school, (2) whether the comic media can help in improving the quality of mathematics learning in primary schools. This research is a qualitative research. This research contains of three sub researches. The comic media that is implemented is an educational comic media. The comic media is implemented in CTL with talking stick variation, Pjbl model with bamboo dancing variation, and CTL model with snowball throwing variation . Comic media developed adapted to the learning model used. Because the learning model used is different, the mathematics learning syntax of the three sub researches is also different. The three sub researches obtaining the same result. Comic media can help in improving the quality of mathematics learning in elementary school even though implemented with different learning model. The conclusions of this research are (1), Comics are given at the beginning of the lesson and students try to understand the material and construct the concept through comics.,(2) Comic media can assist in improving the quality of mathematics learning.